Ответы
Ответ дал:
0
1/(m-1)(m-n) + 1/(1-m)((1-n) - 1/(n-m)(n-1)=
=1/((m-1)(m-n)) + 1/((m-1)(n-1)) +1/((m-n)(n-1))=
=сводим к общему знаменателю=
=(n-1+m-n+m-1)((m-n)(m-1)(n-1))=
в числителе должен был оказаться 0, значит гдето в выражении ошибка
если например
1/(m-1)(m-n) + 1/(1-m)((1-n) + 1/(n-m)(n-1)=
=1/((m-1)(m-n)) + 1/((m-1)(n-1)) -1/((m-n)(n-1))=
=сводим к общему знаменателю=
=(n-1+m-n-m+1)((m-n)(m-1)(n-1))=0((m-n)(m-1)(n-1))=0
Похожие вопросы
1 год назад
1 год назад
10 лет назад
10 лет назад